Predecting Management Potential of MBA Program Applicants - V Srinivasan; Bradley A Hanson (2018)
The Emperical Literature in Decision making suggests that the reliability and validity of MBA admission decisions can be enhanced with the aid of actuarial models that relate measures of managerial success to predictors available from the MBA application folder. Multiple regression analysis was used to relate compensation to adjustment variables and model variables drawn from the MBA application folder. Geographical cost of living index was significantly positively related to compensation. Experience prior to the GMAT showed no relationship to adjusted compensation. The MBA grade point average was positively related to adjusted compensation.
Keywords: Education